MRI and muscle enzymes do not support the diagnosis of local anesthetic myotoxicity: a descriptive case series. Issue 8 (31st May 2021) - Mahyar, Lauren; Neal, Joseph M; Blackmore, C Craig; Jackson, Dane W; Hanson, Neil A; MacDonald, Kevin M; Warren, Daniel; Verdin, Peter J
Abstract : Background: The presence of thigh muscle edema as characterized by increased signal intensity on MRI has been used to support the diagnosis of presumed local anesthetic-induced myotoxicity reported after total knee arthroplasty (TKA) with continuous adductor canal block (CACB). However, neither postoperative baseline imaging appearance nor muscle enzyme values have been described in conjunction with this clinical scenario. Thus, the usefulness of MRI or enzymatic biomarkers of muscle injury for supporting the diagnosis of local anesthetic myotoxicity is unknown. Methods: This descriptive case series documents postoperative MRI appearance of the ipsilateral upper leg, plus preoperative and postoperative creatine phosphokinase and aldolase values in volunteer patients who underwent uncomplicated TKA with CACB. Results: In 27 volunteer patients with no postsurgical evidence of clinically relevant myotoxicity, anterior thigh muscle edema was universally evident on imaging (n=12) and muscle enzyme values (n=19) were normal or only slightly elevated. Conclusions: The non-specificity of these findings suggests that MRI and near normal muscle enzyme levels are of limited diagnostic value when there is clinical suspicion of local anesthetic myotoxicity in the setting of TKA with CACB. Trial registration number: NCT04821245 .